Clinical Cancer Genetics Disparities among Latinos - Marcia Cruz‐Correa; Julyann Pérez‐Mayoral; Julie Dutil; Miguel Echenique; Rafael Mosquera; Keila Rivera‐Román; Sharee Umpierre; Segundo Rodríguez-Quilichini; María González‐Pons; Myrta I. Olivera; Sherly Pardo (2016)
Abstract The three major hereditary cancer syndromes in Latinos (Hereditary Breast and Ovarian Cancer, Familial Adenomatous Polyposis and Lynch Syndrome) have been shown to exhibit geographic disparities by country of origin suggesting admixture‐based disparities. A solid infrastructure of clinical genetics geared towards diagnosis and prevention could aid in reducing the mortality of these cancer syndromes in Latinos. Currently, clinical cancer genetic services in Latin America are scarce. Moreover, limited studies have investigated the mutational spectrum of these cancer syndromes in Latinos resulting in gaps in personalized medicine affecting diagnosis, treatment and prevention. The following commentary discusses available genotype and clinical information on hereditary cancer in Latinos and highlights the limited access for cancer genetic services in Latin America including barriers to genetic testing and alternatives for providing better access to genetic services. In this review, we discuss the status of clinical genetic cancer services for both US Latinos and those Latinos living in Latin America.